PENINGKATAN PERANAN KELUARGA DALAM PENANGANAN MASALAH BALITA GIZI KURANG DI KELURAHAN MALEER KECAMATAN BATUNUNGGAL KOTA BANDUNG - Didi Supriyadi (Politeknik Kesejahteraan Sosial Bandung, 2013)
Abstract This research of the improvement to the role of the family in an effort the handling of the problem less nutrition’s toddlers in Kelurahan Maleer Kecamatan Batununggal Kota Bandung. Type of research design is taken from an action research. The purpose of use of action research is to develop the most efficient method in an effort to strengthen the role of families in tackle the problem of less nutrition's toddlers. Sources of data obtained by the authors in the research through observation, interviews, documentation studies and participatory assessment techniques in order to obtain design models increased role of the family in the treatment of less nutrition toddlers. Then the data was analyzed qualitatively. The results showed that the implementation of the model increased the role of the family in the treatment of less nutrition toddlers include increased understanding of the role of the family in the treatment of less nutrition toddlers and family relationship development with source systems have a positive impact in increasing the role of the family. However, efforts to improve the model by increasing capacity posyandu in providing support to the family of children through training and mentoring as well as maintaining relationships with the source system must be improved. Keywords: role of the family, toddlers, nutrition, family, malnutrition toddlers Abstrak Penelitian ini tentang upaya meningkatkan peranan keluarga dalam penanganan masalah balita gizi kurang di Kelurahan Maleer Kecamatan Batununggal Kota Bandung. Jenis desain penelitian yang diambil adalah action research atau penelitian tindakan. Adapun tujuan penggunaan action research adalah mengembangkan metode yang paling efisien dalam upaya memperkuat peranan keluarga dalam penanggulangan masalah balita gizi kurang. Sumber data dalam penelitian diperoleh penulis melalui observasi, wawancara, studi dokumentasi dan teknik asesmen partisipatif guna memperoleh rancangan model peningkatan peranan keluarga dalam penanganan balita gizi kurang. Kemudian data dianalisis dilakukan secara kualitatif. Hasil penelitian menunjukan bahwa implementasi model peningkatan peranan keluarga dalam penanganan balita gizi kurang berupa peningkatan pemahaman tentang peranan keluarga dalam penanganan balita gizi kurang dan pengembangan hubungan keluarga dengan sistem sumber berdampak positif dalam peningkatan peranan keluarga. Namun demikian, upaya perbaikan model berupa peningkatan kapasitas kader posyandu dalam pemberian dukungan terhadap keluarga balita melalui pelatihan dan pendampingan serta menjaga relasi dengan sistem sumber harus selalu ditingkatkan. Kata kunci: peran keluarga, balita, gizi, keluarga, balita gizi kurang